Examining temporal effects on cancer risk in the international nuclear workers' study. Issue 6 (15th March 2017) - Daniels, Robert D.; Bertke, Stephen J.; Richardson, David B.; Cardis, Elisabeth; Gillies, Michael; O'Hagan, Jacqueline A.; Haylock, Richard; Laurier, Dominique; Leuraud, Klervi; Moissonnier, Monika; Thierry‐Chef, Isabelle; Kesminiene, Ausrele; et al.
Abstract : The paper continues the series of publications from the International Nuclear Workers Study cohort that comprises 308, 297 workers from France, the United Kingdom and the United States, providing 8.2 million person‐years of observation from a combined follow‐up period (at earliest 1944 to at latest 2005). These workers' external radiation exposures were primarily to photons, resulting in an estimated average career absorbed dose to the colon of 17.4 milligray. The association between cumulative ionizing radiation dose and cancer mortality was evaluated in general relative risk models that describe modification of the excess relative risk (ERR) per gray (Gy) by time since exposure and age at exposure. Methods analogous to a nested‐case control study using conditional logistic regression of sampled risks sets were used. Outcomes included: all solid cancers, lung cancer, leukemias excluding chronic lymphocytic, acute myeloid leukemia, chronic myeloid leukemia, multiple myeloma, Hodgkin lymphoma and non‐Hodgkin lymphoma. Significant risk heterogeneity was evident in chronic myeloid leukemia with time since exposure, where we observed increased ERR per Gy estimates shortly after exposure (2–10 year) and again later (20–30 years). We observed delayed effects for acute myeloid leukemia although estimates were not statistically significant. Solid cancer excess risk was restricted to exposure at age 35+ years and also diminished for exposure 30 years prior to attained age. Persistent or late effects suggest additional follow‐up may inform on lifetime risks. However, cautious interpretation of results is needed due to analytical limitations and a lack of confirmatory results from other studies. Abstract : What's new? Being exposed to radiation is harmful, and practices are in place to protect people from high doses in the workplace. Therefore, nuclear workers generally experience only low daily doses of radiation, but how does this affect their lifetime cancer risk? To find out, researchers have pooled data from more than 300, 000 workers in France, the UK, and the USA, in some cases covering a 60‐year follow‐up. These authors investigated the relationship between age at exposure, time since exposure and cancer risk. They observed an increased risk of chronic myeloid leukemia 2–10 years after exposure, and again 20–30 years afterward.